New detected uncertainties in the design of foundations for offshore Wind Turbines. (February 2019) - Luengo, Jorge; Negro, Vicente; García-Barba, Javier; López-Gutiérrez, José-Santos; Esteban, M. Dolores
Abstract: In 2014, the Renewable Energy Journal published innovative research where the authors showed the results obtained in work where the design of support structures and foundations in marine based wind farms were questioned. The uncertainties in the design were then justified by the "limited" field experience and in the review of the standards and recommendations existing at that time. Fundamentally, an analysis was made of the ratio between useful life and the probability of failure, the wave theories to be used, the hydrodynamics of Morison, Froude-Krylov and diffraction domains, together with the scouring phenomena processes and consequent protection of structural items. Using the knowledge gained during these three years, the research work herein presented covers further reflections such as the nonlinearity in wave mechanics, its effects on orbital seabed velocities, variation in the behaviour of the Keulegan-Carpenter number (KC), impact on scour in the KC-6 equation, the analysis of statistics of forces applied to load combinations in structures at depths in excess of fifty metres, taking giant steps in offshore engineering and leaving behind classical maritime engineering techniques. Highlights: Identified uncertainties in standards for design of offshore wind foundations. Analysed the impact of using non-linear wave theories instead of linear ones. Different order of the scour phenomenon are distinguished. Duration of storms and the number of actives waves impact the undulatory period. Discussion about the use of Hs)1 year, Hs)5 year, Hs)50 year and T-1, 0.